2012
DOI: 10.1590/s1983-51752012000100014
|View full text |Cite
|
Sign up to set email alerts
|

Gluteoplastia de aumento: experiência do Serviço de Cirurgia Plástica Dr. Ewaldo Bolivar de Souza Pinto

Abstract: Background: The buttocks are formed by muscles responsible for leg movement, the largest being the gluteus maximus. Moreover, the buttocks have secondary sexual function: they are an erogenous area and a symbol of fertility, and are employed in advertising for male-oriented consumer products. Women with bigger buttocks arouse greater attraction and sexual desire, which has driven the demand for augmentation gluteoplasty with silicone implants. This study analyzed the authors' experience with the XYZ augmentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
1
0
1
Order By: Relevance
“…As complicações e intercorrências mais frequentes são a dor, deiscência da ferida, seroma, fibrose e infecção. 6,7 Vergara, Amezcua 8 relataram suas experiências na realização de aumento glúteo pela técnica intramuscular em 160 casos ao longo de 15 anos, onde ocorreram complicações em 16 ou seja (10%) dos 160 pacientes, seroma apresentado em 7 (4%), assimetria em 4 (2,66%), contratura capsular em 3 (2%), hipercorreção em 1 (0,66%), e ruptura do implante em 1 (0,66%).…”
Section: 7unclassified
“…As complicações e intercorrências mais frequentes são a dor, deiscência da ferida, seroma, fibrose e infecção. 6,7 Vergara, Amezcua 8 relataram suas experiências na realização de aumento glúteo pela técnica intramuscular em 160 casos ao longo de 15 anos, onde ocorreram complicações em 16 ou seja (10%) dos 160 pacientes, seroma apresentado em 7 (4%), assimetria em 4 (2,66%), contratura capsular em 3 (2%), hipercorreção em 1 (0,66%), e ruptura do implante em 1 (0,66%).…”
Section: 7unclassified
“…It is widely adopted by the medical community, being used for bone reconstitution and corrections in neurosurgery, ophthalmology, and traumatology mainly due to its biocompatibility, stability at the application site, and low risk of complications and migration. 1,[5][6][7] It is well known that PMMA microsphere filling results in tissue growth by the body itself. The dramatic increase in product quality in recent years has directly influenced the decreasing complication rates.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely adopted by the medical community, being used for bone reconstitution and corrections in neurosurgery, ophthalmology, and traumatology mainly due to its biocompatibility, stability at the application site, and low risk of complications and migration. 1 , 5 7 …”
Section: Introductionmentioning
confidence: 99%
“…1 There is a consensus among plastic surgeons that the best plane for placing the implants is the intramuscular plane. 2 There are, in fact, four planes for placing gluteal implants, namely the subcutaneous, subfascial, intramuscular, and submuscular planes. Studies have shown that the intramuscular plane has the lowest rate of complications.…”
mentioning
confidence: 99%